The influence of welfare spending on national immunization outcomes: A scoping review. Issue 6 (August 2021) - Walker, Mary Ellen; Tchir, Devan; Szafron, Michael; Anonson, June
Background: National policies influence the environments in which people live, but the ways in which these national policies influence people's health are not well understood. Welfare spending is one national policy that may influence population health. While some research indicates higher levels of welfare investment may positively influence health, mixed findings contradict this conclusion. These mixed results examining the link between welfare policies and health may be better understood by investigating the relationship between welfare spending and preventative health interventions, such as immunization.Objective: This article's purpose is to summarize the literature studying the relationship between national welfare spending and immunization outcomes.Design: This scoping review used the Joanna Briggs scoping review method.Data sources: The scoping review utilized scholarly databases and a focused gray literature search to find research articles that explored relationships between welfare spending and immunization outcomes.Review methods: Data was extracted from articles, including themes, aims, populations, years of study, methods, and findings. The articles' themes were further analyzed with a word cloud and principal component analysis to determine which themes were more likely to coincide in the literature.Results: Seven articles were included in the review. Most of these articles did not address the relationship between welfare spending or policy and immunizations directly or with rigorous methods.Conclusions: Ultimately, the results of the scoping review suggest a lack of literature regarding the relationship between welfare spending and immunization outcomes. Further research is needed to understand the impacts of national welfare spending on immunization outcomes.